2022
DOI: 10.1097/corr.0000000000002308
|View full text |Cite
|
Sign up to set email alerts
|

Is the Addition of Anaerobic Coverage to Perioperative Antibiotic Prophylaxis During Soft Tissue Sarcoma Resection Associated With a Reduction in the Proportion of Wound Complications?

Abstract: Background Wound complications are common after resection of soft tissue sarcomas, with published infection rates ranging from 10% to 35%. Multiple studies have reported on the atypical flora comprising these infections, which are often polymicrobial and contain anaerobic bacteria, and recent studies have noted the high prevalence of anaerobic bacterial infections after soft tissue sarcoma resection [26,35]. Based on this, our institution changed clinical practice to include an antibiotic with anaerobic covera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…The current study by Ramsey et al [10] found that the addition of anerobic coverage (most often metronidazole) to the standard prophylactic regimen (usually a first-generation cephalosporin) during STS resection was associated with a lower odds of major wound complications and no documented adverse reactions attributable to the additional antibiotics. The authors acknowledge that the work is preliminary, but it certainly indicates follow-up studies that can help us determine the best methods for preventing surgical site infection in patients undergoing STS resection.…”
Section: Where Are We Now?mentioning
confidence: 63%
See 4 more Smart Citations
“…The current study by Ramsey et al [10] found that the addition of anerobic coverage (most often metronidazole) to the standard prophylactic regimen (usually a first-generation cephalosporin) during STS resection was associated with a lower odds of major wound complications and no documented adverse reactions attributable to the additional antibiotics. The authors acknowledge that the work is preliminary, but it certainly indicates follow-up studies that can help us determine the best methods for preventing surgical site infection in patients undergoing STS resection.…”
Section: Where Are We Now?mentioning
confidence: 63%
“…Future studies should focus on this anatomic site compared with others. This may add an important variable to support the indication for the protocol suggested by Ramsay et al [10].…”
Section: Where Do We Need To Go?mentioning
confidence: 90%
See 3 more Smart Citations